2015
DOI: 10.5993/ajhb.39.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss Attitudes and Social Forces in Urban Poor Black and White Women

Abstract: Objective To explore differences between Blacks and Whites in perceived influences on weight-related behaviors among obese urban poor women. Methods Participants (N = 27) received physician referrals to a weight loss program located in Federally Qualified Health Centers and either never attended or stopped attending. We conducted in-depth, in home interviews using a script informed by focus groups, pilot discussions, and the theory of planned behavior (TPB) to learn about participants’ weight loss attitudes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Despite the high levels of overweight and obesity in our study sample, participants reported moderate levels of body satisfaction, which is consistent with previous studies that found positive body image perceptions among obese black women (6,7,9,). Yet, body satisfaction was not related to motivation or confidence in ability to lose weight.…”
Section: Discussionsupporting
confidence: 92%
“…Despite the high levels of overweight and obesity in our study sample, participants reported moderate levels of body satisfaction, which is consistent with previous studies that found positive body image perceptions among obese black women (6,7,9,). Yet, body satisfaction was not related to motivation or confidence in ability to lose weight.…”
Section: Discussionsupporting
confidence: 92%
“…[20][21][22] In addition, racial/ethnic minorities have been found to report less social pressure to lose weight, while also having lower rates of engagement in formalized weight loss programs and ultimate weight-loss success. [22][23][24][25][26] The literature exploring racial/ ethnic differences in motivation for physical activity has proven to be relatively more fruitful, which is likely related to the fact that racial/ethnic minorities have consistently been found to have lower rates of physical activity. [27][28] For example, Egli and colleagues 29 explored racial differences across 14 different exercise motivation subscales (including intrinsic and extrinsic motivators) among a sample of college students and found significant racial differences for eight of the exercise motivators, suggesting that specific motivators for physical activity vary substantially across races.…”
Section: Introductionmentioning
confidence: 99%
“…15 In fact, experimental research has demonstrated a powerful influence of cues on eating behavior, 16 and our previous research suggests that food cues are pervasive in the lives and homes of obese urban poor women. 17 Lifestyle interventions often do provide participants with information about cues and how to "take charge of what's around you", 18 but the field of automaticity has shown that humans are largely unaware of cues and their influence on desires and behaviors. 15,19 Establishing novel methods to identify, evaluate, and quantify the contexts to which obese black compared to obese white women are exposed may lead to valuable insight into the cues that trigger obesogenic behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,20,21 For example, urban poor black women often report being part of social networks that support obesity and intake of foods that are high in fat, sodium, and sugar. 17,22 Urban poor white women, on the other hand, report social networks that support and encourage small body sizes. 17,22 While it is well known that internal and external factors affect weight-related behavior, 23 to our knowledge, these factors have not been extensively studied in the urban poor women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation